Impact of COVID-19 on Financial Reporting in Latin America and the Caribbean - World Bank (Washington, DC:, 2022)
The COVID-19 pandemic represents the largest economic shock the world economy has witnessed in decades, causing a collapse in global activity. Nevertheless, there are signs that global activities are stabilizing, and have picked up in many large emerging markets and developing economies (EMDEs). Global growth is set to reach 5.6 percent in 2021, however, growth will be uneven and concentrated in a few major economies, with most of the EMDEs lagging behind. The Latin America and the Caribbean (LAC) region has been one the most severely affected in economic and social terms. Its estimated decline in GDP exceeds both that of advanced and developing economies. This study on the impact of COVID-19 on financial reporting in LAC was conducted with the following objectives: (i) Analyze whether the financial impact of COVID-19 is reflected in the financial reports of a sample of countries of the LAC region; (ii) assess whether the balance sheet of the countries included in the sample can convey the long-term fiscal sustainability of the government, reflecting the fiscal risks associated with the financial performance and financial position of the government in the context of the COVID-19 pandemic; and (iii) determine whether the notes to the financial statements are being used to present the financial information in a transparent manner by explaining materially large figures and significant changes caused by the COVID-19 pandemic.